Comparative Transcriptome Analyses of Longissimus thoracis Between Pig Breeds Differing in Muscle Characteristics - Cai, Chunbo; Li, Meng; Zhang, Yanwei; Meng, Shan; Yang, Yang; Gao, Pengfei; Guo, Xiaohong; Cao, Guoqing; Li, Bugao (Frontiers in Genetics, 2020)
The two breeds, Mashen (MS, a northern China breed) and Large White (LW, a western lean breed) pigs, show important phenotypic differences in growth, adaptability, intramuscular fat (IMF) content and energy metabolism since early developmental stage. The main aim of this study was the evaluation of longissimus thoracis muscle transcriptome profile of both genetic types to identify genes, pathways responsible for their differentiated phenotype. Longissimus thoracis of MS and LW pigs were sampled at 0 day (early stage), 90 days (middle stage), and 180 days (later stage) after birth. A total of 3,487 differentially expressed genes (DEGs) were identified at the three time points. Sample clustering analysis revealed the relatively slower growth rate of MS than LW pigs. Gene expression pattern analysis revealed that multicellular organism growth genes (GHSR, EZR, FOXS1, DRD2, SH3PXD2B, CSF1, TSHR) were involved in the fast growth rate of LW pigs at early stage. Furthermore, DEGs (ACACA, ACSF3, OXSM, CBR4, HSD17B8) functionally related to fatty acid synthesis revealed that IMF accumulation occurred around 90 days and up to 180 days. These DEGs provided valuable resource to study the phenotypic difference in longissimus thoracis muscle between MS and LW pigs.